Efficient decoding approach for NB-LDPC codes with short blocklength - Yang, Xiao; Jiang, Ming; Li, Zhengyi; Wang, Chen; Zhao, Chunming (IET communications, 2019)
In this study, the authors propose a parallel concatenated decoding (PCD) scheme for short non-binary low-density-parity-check (NB-LDPC) codes. It consists of a reduced trellis extended min-sum (R-TEMS) algorithm which efficiently reduces the check node updating complexity over high-order Galois fields and a low complexity ordered statistic decoding aided by partial cyclic redundancy check bits. The R-TEMS algorithm has a negligible performance loss and noticeable reduction in decoding complexity with respect to the trellis-based EMS (TEMS) algorithm. Besides, the PCD shows a close error-correction performance when compared with other concatenated decoding schemes for NB-LDPC codes. It achieves a coding gain about 0.5 dB with reasonable complexity contrasted with the Q-ary sum–product algorithm for high-rate short NB-LDPC codes over GF(256).